Foot deformation analysis with different load-bearing conditions to enhance diabetic footwear designs. - Liying Zhang (PLoS ONE, 2022)
In-depth analyses of foot surface measurements upon weight bearing are crucial to understand how the dorsal and plantar surfaces of the foot deform during motion to enhance the fit of footwear, which is particularly important for diabetic patients with stringent fit requirements to redistribute the plantar weight forces. This study analyzes diabetic foot deformations under 3 different weight bearing conditions (no weight bearing, half weight bearing, and 80% weight bearing) by using a novel foot scanning method that enables efficient scanning of the dorsal and plantar surfaces of the foot simultaneously. The feet of 48 patients with diabetes mellitus (DM) are scanned. With increased load on the feet, the width of the forefoot increases by 9.7%-10.4%, height of the midfoot decreases by 15.1%-18.2%, forefoot and midfoot rotate to the medial side by 16.9%-23.9% while the rearfoot rotates to the lateral side by 15.2% simultaneously, and the plantar of the foot increases contact with the floor by 11.4%-23.0%. Gender differences in foot shape are also found between males and females, males have a broader foot than females for the same foot length. Precise anthropometric information of foot changes and deformation therefore enables adequate foot protection, fit and comfort when designing footwear. This research contributes to shoe design considerations that focus on the deformation of the foot under different loads.